2022
DOI: 10.3390/plants11151978
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Microbial Fertilizers on Growth and Rhizosphere Soil Properties of Corn in Newly Reclaimed Land

Abstract: Land reclamation may expand the supply of usable land for food security. Soil microorganisms have been considered as an amendment in immature soil to improve its quality. However, different microbial fertilizers’ effects on plant growth in immature soil have largely been unexplored. In order to evaluate the effects of different microbial fertilizers on immature soil, the soil quality and microbial community structure of corn rhizosphere soil samples under different microbial fertilizers were investigated. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 31 publications
5
10
0
Order By: Relevance
“…This may be due to the proportion of microaggregates (<0.25 mm) of soil decreased by repeat application of CCF [ 30 ]. In agreement with the results of this study, a similar observation of an increase in OMC was observed by Renet al [ 17 ] and Li et al [ 4 , 27 ]. Furthermore, other studies have also shown that the soil OMC could be effectively improved by planting winter legume crops, returning crop stems and stalks to the field, comprehensively utilizing agricultural and animal husbandry wastes, and making compost by using rural litter and gully soil [ 28 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ].…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…This may be due to the proportion of microaggregates (<0.25 mm) of soil decreased by repeat application of CCF [ 30 ]. In agreement with the results of this study, a similar observation of an increase in OMC was observed by Renet al [ 17 ] and Li et al [ 4 , 27 ]. Furthermore, other studies have also shown that the soil OMC could be effectively improved by planting winter legume crops, returning crop stems and stalks to the field, comprehensively utilizing agricultural and animal husbandry wastes, and making compost by using rural litter and gully soil [ 28 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ].…”
Section: Resultssupporting
confidence: 94%
“…The results from this study indicated that there was no significant difference in soil pH between the addition of commercial organic fertilizer, chemical compound fertilizer, and the control of corn rhizosphere soil during 2019 to 2021. However, compared with the control, the soil pH was slightly increased by PMMR-OF, SM-OF, and CCF from pH 5.59 to pH 5.61–6.64 in 2019–2021, excluding a slight decrease by SM-OF to pH 5.40–5.54 in 2019, which is in coordination with our previous studies [ 13 , 17 , 27 , 28 , 29 ], and indicated that the pH of soil can be changed to a certain extent. Furthermore, the soil OMC was significantly increased by all the test commercial organic fertilizers in 2019–2021.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…For example, Zhang et al (2018) showed that yield of facility tomato was improved after the Frontiers in Microbiology 12 frontiersin.org application of microbial fertilizers (especially ABA-2). Li et al (2022c) reported that the application of Tuzangjin microbial fertilizer, carbonergic microbial agent, and seaweed fertilizer resulted in a greater promotion effect on corn production in newly reclaimed land, and the applied amount of microbial fertilizers could be reduced as the soil fertility improves. The soil properties in the packchoi field were differentially affected by different treatments, and the effect was dependent on the soil parameters and the kind of fertilizer.…”
Section: Discussionmentioning
confidence: 99%